Analisis Perbandingan Pegawai Tetap dan Pegawai Outsourcing Bagian Kebersihan Ditinjau dari Pemberdayaan, Kepuasan Kerja dan Komitmen Organisasi - Cucu Hodijah; Rika Solihah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
This study aims to analyze the Comparison of Permanent Employees with Employees Outsourcing the Cleanliness Section viewed from Empowerment, Job Satisfaction and Organizational Commitment. The research hypothesis is that there are differences between Permanent and Outsourcing Employees seen from Empowerment, Job Satisfaction and Organizational Commitment. Research is a quantitative study using a comparative / difference approach. Data collected using a questionnaire with a Likert scale. Data processing using one way ANOVA and Independent Sample t-test and descriptive analysis data using the average technique. The results showed that there were differences in terms of Empowerment, Job Satisfaction and Organizational Commitment between Permanent Employees and Outsourcing Employees, where the Permanent Employee Organizational Commitment variable had a higher value than the Outsourcing Officer